The Effects of Exogenous Auxins on Endogenous Indole-3-Acetic Acid Metabolism (The Implications for Carrot Somatic Embryogenesis). - Ribnicky, D. M. (1996)
The effect of auxin application on auxin metabolism was investigated in excised hypocotyl cultures of carrot (Daucus carota). Concentrations of both free and conjugated indole-3-acetic acid (IAA), [2H4]IAA, 2,4-dichlorophenoxyacetic acid, and naphthaleneacetic acid (NAA) were measured by mass spectroscopy using stable-isotope-labeled internal standards. [13C1]NAA was synthesized for this purpose, thus extending the range of auxins that can be assayed by stable-isotope techniques. 2,4-Dichlorophenoxyacetic acid promoted callus proliferation of the excised hypocotyls, accumulated as the free form in large quantities, and had minor effects on endogenous IAA concentrations. NAA promoted callus proliferation and the resulting callus became organogenic, producing both roots and shoots. NAA was found mostly in the conjugated form and had minor effects on endogenous IAA concentrations. [2H4]IAA had no visible effect on the growth pattern of cultured hypocotyls, possibly because it was rapidly metabolized to form inactive conjugates or possibly because it mediated a decrease in endogenous IAA concentrations by an apparent feedback mechanism. The presence of exogenous auxins did not affect tryptophan labeling of either the endogenous tryptophan or IAA pools. This suggested that exogenous auxins did not alter the IAA biosynthetic pathway, but that synthetic auxins did appear to be necessary to induce callus proliferation, which was essential for excised hypocotyls to gain the competence to form somatic embryos.